The Needle and the Damage Done: An Exploratory Analysis of Wisconsin's Heroin Epidemic - Trainor, Clare; Robson, Natalee; McHugh, Jon (My University, 2016)
Since the early 2000’s, Wisconsin has experienced an explosive growth in the illicit use of heroin, leading to an epidemic of this highly addictive opioid. This project will attempt to identify hotspots of the use of heroin and other related opioids at the state’s zip code level since the onset of the epidemic. We will further explore its association with income, age, and race by overlaying datasets of these additional variables with our zip code level data. With this information, we will create graphics that inform the general public in regards to where heroin and related narcotic use is present, what factors are correlated with its use, and what is being done to stop it. By overlaying socioeconomic variables, we will be able to identify demographic and social factors associated with the abuse of these illicit drugs and compare different areas in Wisconsin. Once we have this information, the graphics we make will educate people about the various aspects of the heroin epidemic in Wisconsin. These graphics may also be beneficial for law enforcement, drug abuse prevention and rehabilitation programs.
Includes figures, maps, bibliography
Keywords: Addiction; Opioid; Epidemic; Heroin; Wisconsin